2022
DOI: 10.3889/oamjms.2022.8352
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lipid Peroxidation-antioxidant Defense Systems in Rats under Radiation Exposure

Abstract: Abstract BACKGROUND: Experimental data on the effect of a high dose of gamma radiation 6 Gy on the activity of antioxidant defense enzymes and lipid peroxidation products (LPO) are presented immunocompetent organs in the body of animals in the experiment. It was found that the effect of ionizing radiation led to an increase in the level of diene conjugates (DC) and malondialdehyde (MDA), inhibition of the activity of catalase (CАT) and glutathione peroxidase (GlP), glutathione reductase (GlR) enzymes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results showed that irradiation at a dose of 6 Gy increased MDA concentrations significantly by 5.5 times in the liver and 2.3 times in the spleen compared to controls. A previous study by Okassova et al (2022) reported that gamma radiation could significantly increase MDA levels in the liver by 1.76 times and spleen by 1.4 times in animals exposed to gamma radiation. Concentration of MDA in plasma is an important biomarker in radiation exposure to assess oxidative stress and its impact on lipid peroxidation levels (Maurya et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…The results showed that irradiation at a dose of 6 Gy increased MDA concentrations significantly by 5.5 times in the liver and 2.3 times in the spleen compared to controls. A previous study by Okassova et al (2022) reported that gamma radiation could significantly increase MDA levels in the liver by 1.76 times and spleen by 1.4 times in animals exposed to gamma radiation. Concentration of MDA in plasma is an important biomarker in radiation exposure to assess oxidative stress and its impact on lipid peroxidation levels (Maurya et al, 2021).…”
Section: Discussionmentioning
confidence: 89%